Auditing cybersecurity risks considering the information renaissance and its impact on the continuity of companies - Wahhab, Asaad Mohammed Ali; Jawad, Baneen Hassoun; Alajeli, Emad Hamza Abd (Technium Social Sciences Journal, 2022)
The research aims to identify the role of the external auditor in auditing cybersecurity risks and the size of the cybersecurity risks to which Iraqi companies are exposed and to determine the procedures of the external auditor and Iraqi audit offices in auditing cybersecurity risks and their adequacy, in addition to knowing the impact of cybersecurity risks on the continuity of Iraqi companies. Eighty-five questionnaires were distributed to a sample of external auditors in auditing offices who have experience auditing electronic accounting systems in Iraq, and 77 questionnaires were retrieved from them that are valid for analysis using the SPSS statistical program. There is a relative development in the use of electronic accounting and administrative systems by Iraqi joint stock companies. There is a clear impact on the continuity of companies due to cybersecurity risks that cannot be avoided, as well as the lack of sufficient experience among many work teams in audit offices to audit cybersecurity risks.